Empowering universities through health promoting university for tackling the non-communicable disease in the digital era - Supriyati Supriyati; Riskiyana Sukandhi Putra; Yayi Suryo Prabandari (Journal of Community Empowerment for Health, 2022)
Non-communicable diseases are responsible for 71% of the premature death in the worldwide. Unfortunately, 77% of those premature death was occurred in the developing countries include Indonesia. On the other hand, Universities are potentially to empower for tackling the non-communicable disease risk factors. This study was aimed to explain the process on how to empower university for tackling the non-communicable diseases risk factors through health promoting university (HPU). This study applied action research and had been done in 2019 - 2021. The population were Indonesian universities, and sample were 40 universities that develop HPU in this period. Data was collected through observation and unstructured interview. Observation had been performed in the 25 universities. Meanwhile unstructured interview carried out with 34 respondents. Data was analysed descriptively. The process of the HPU development and the focus program were varied. Many factors contributed to the process of the HPU development, such as the HPU development strategies, the university leader’s commitment, networking, social capital, and participant’s capacity on the health promotion. The HPU development strategy performed in 2022 was the most structured and comprehensive. Generally, the HPU development had been conducted by optimizing the information technology. In addition, mentoring system, leader commitment, and the networking were strongly contributed the succeed of the HPU development. This study emphasizes the important of the university leader’s awareness toward health and the potential resources of the university for tackling the non-communicable disease risk factors.